Understanding language teachers' enactment of content through the use of centralized curriculum materials. Issue 5 (20th October 2018) - Li, Zhan; Harfitt, Gary
ABSTRACT: This study examines a timely yet under-studied area of language curriculum implementation in classroom settings. It explores teachers' enactment of content by focusing on the use of prescribed textbooks for planning instruction in higher education by teachers of English as a foreign language in mainland China. This qualitative case study involved two Chinese teachers of English as a foreign language. Drawing on data from interviews with the teachers and their students, lesson observations and documents from one semester, the teachers' use of curriculum materials was fleshed out into four interactional processes: reading, evaluating, appropriating and adapting . This study attempts to uncover the mediated relationships among the teachers, students and curriculum materials via these four processes. By conceptualising this ubiquitous pedagogical practice, our understanding of language teachers' enactment of curriculum materials is deepened. Theoretical and practical implications are also addressed.